Pengaruh Panjang Rantai Karbon dan Derajat Ketidakjenuhan terhadap Karakteristik Pembakaran Droplet Asam Lemak Tunggal - Ibadurrohman, Ibrahim Ahmad; Hamidi, Nurkholis; Yuliati, Lilis (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
This study aimed to investigate the effect of the different carbon chain lengths and the degree of unsaturation of six fatty acids as the constituent of vegetable oils. The droplet combustion was carried out at an ambient temperature and atmospheric pressure. The variation in the carbon chain length and the degree of unsaturation resulted in different physical and chemical properties of the fuel, which affect the droplet combustion characteristics. The increase of the carbon chain length results in longer ignition delay times and shorter burning durations, as well as higher droplet temperatures, burning rate constant, and specific power output. Conversely, an increase in the degree of unsaturation with the presence of double bond results in shorter ignition delay and longer burning duration, as well as higher droplet temperatures, but lower burning rate constant and specific power output. The droplet diameter evolution divides the combustion period into unsteady burning zones and quasi-linear burning zones. The flame dimension of unsaturated fatty acid is higher due to the soot formation at the top of the flame. A bluish flame related to the higher oxygen content in the molecule can be observed in saturated fatty acids. The short-chain saturated fatty acid has a large non-luminous zone because they are rich in oxygen. In contrast, the long-chain saturated fatty acid has a narrow non-luminous zone with high flame radiation.